ASĀLĪB AL-ADʿIYYAH FĪ AL-QURʾĀN WA AL-AḤĀDIṮ AL-NABAWIYYAH - Muhammad Mukhlis (UIN ANTASARI, 2020)
This study aims to (1) compare the style of language in the prayers in the Al-Quran dan Hadist Nabi SAW, (2) show the style of language used in the prayers in the Al-Quran dan Hadist Nabi SAW, (3) show the suitability of Balaghah and Uslubiyah on Prayers in the Al-Quran dan Hadist Nabi SAW.The results of this analysis indicate that there are several styles of language used in prayers in the Al-Quran and Hadist. The style of language from the side of the lexicon is Isti'azah, Istigfar, ikr, Su'al, and Nida‟. As for the sentence structure, namely Climax and Anticlimax. Meanwhile, in terms of direct or indirect meaning, namely: (Ishtia’arah, Mubalaghah, Tasybih, Kinayah, Majaz, Jinas)